Araloside C attenuates atherosclerosis by modulating macrophage polarization via Sirt1-mediated autophagy - Luo, Yun (Aging (Albany NY), 2020)
Atherosclerosis-related cardiovascular disease is still the predominant cause of death worldwide. Araloside C (AsC), a natural saponin, exerts extensive anti-inflammatory properties. In this study, we explored the protective effects and mechanism of AsC on macrophage polarization in atherosclerosis in vivo and in vitro. Using a high-fat diet (HFD)-fed ApoE-/- mouse model and RAW264.7 macrophages exposed to ox-LDL, AsC was evaluated for its effects on polarization and autophagy. AsC significantly reduced the plaque area in atherosclerotic mice and lipid accumulation in ox-LDL-treated macrophages, promoted M2 phenotype macrophage polarization, increased the number of autophagosomes and modulated the expression of autophagy-related proteins. Moreover, the autophagy inhibitor 3-methyladenine and BECN1 siRNA obviously abolished the antiatherosclerotic and M2 macrophage polarization effects of AsC. Mechanistically, AsC targeted Sirt1and increased its expression, and this increase in expression was associated with increased autophagy and M2 phenotype polarization. In contrast, the effects of AsC were markedly blocked by EX527 and Sirt1 siRNA. Altogether, AsC attenuates foam cell formation and lessens atherosclerosis by modulating macrophage polarization via Sirt1-mediated autophagy.